Targeting the innate immune receptor TLR8 using small‐molecule agents. Issue 7 (6th July 2020) - Sakaniwa, Kentaro; Shimizu, Toshiyuki
Abstract : The innate immune receptor TLR8 can be positively or negatively regulated by small chemical ligands. Structural views of agonist‐bound and antagonist‐bound forms have revealed the mechanisms underlying agonism and antagonism. Abstract : Toll‐like receptors (TLRs) are pattern‐recognition receptors that initiate innate immune responses. Among the TLRs, TLR8 (and TLR7) recognizes single‐stranded RNA to mediate downstream signals. In recent years, intensive X‐ray crystal structural analyses have provided atomic insights into structures of TLR8 complexed with various agonists or antagonists. Here, structural knowledge of the activation and inactivation mechanisms of the ligands is reviewed. In addition, the potential clinical applications of TLR ligands are examined.